The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.7150/ijms.45856
|View full text |Cite
|
Sign up to set email alerts
|

HTRA1 Variants and the Interaction with Smoking Confer the Genetic Susceptibility to Ischemic Stroke

Abstract: High temperature requirement protein A1 (HtrA1) was identified as the causative gene of autosomal recessive arteriopathy and associated with lacunar ischemic stroke (IS) in European. This study aimed at evaluating the association of HTRA1 with IS and four tagging single-nucleotide polymorphisms (SNPs) were genotyped in a cohort of 4,098 Chinese. The mRNA level of HTRA1 in 72 IS cases and 72 hypertension controls were measured and compared. In whole population, SNP rs2268350 (C>T) was significantly associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Several studies have shown that heterozygous HTRA1 mutations are closely related to cerebral small vessel disease (SVD), small-vessel ischemic stroke and lacunar stroke [18][19][20][21][22][23]. Our previous study also showed that HTRA1 variants might confer the genetic susceptibility to stroke [24]. However, hereditary stroke attributable to HTRA1 gene constitutes only a small proportion of all strokes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that heterozygous HTRA1 mutations are closely related to cerebral small vessel disease (SVD), small-vessel ischemic stroke and lacunar stroke [18][19][20][21][22][23]. Our previous study also showed that HTRA1 variants might confer the genetic susceptibility to stroke [24]. However, hereditary stroke attributable to HTRA1 gene constitutes only a small proportion of all strokes.…”
Section: Introductionmentioning
confidence: 99%
“…Our study also concluded that rs2250889 would increase the susceptibility to IS in smokers. More interestingly, the study found that HTRA1 rs2268350 was significantly associated with IS in drinkers ( 8 ). In contrast, in this study, rs2250889 was related to the increased susceptibility to IS in non-drinkers, suggesting that rs2250889 may be a new locus on MMP-9 for predicting IS risk.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ALDH7A1 rs12514417 polymorphism may increase the risk of IS in individuals exposed to alcohol ( 7 ). OPG SNP T245G is associated with enhanced IS risk among the Chinese ( 8 ). At present, the research on post-genome-wide association study (GWAS) is ongoing, which mainly studies whether genetic variants associated with different disease phenotypes exert their pathogenicity, and it is a means of exploring the relationship between gene polymorphisms and disease risk.…”
Section: Introductionmentioning
confidence: 99%
“…Another study demonstrated that SNPs in PITX2 significantly reduced the risk of IS in Chinese Han males ( 2 ). In addition, SNPs in HTRA1 were significantly associated with the risk of IS among Chinese Han smokers ( 5 ). In our study, analysis results illustrated that rs243849 in MMP2 was associated with evidently increased IS risk in Chinese drinking population under allelic, co-dominant, dominant and additive genetic models.…”
Section: Discussionmentioning
confidence: 99%
“…As a multifactorial complex neurological disorder, stroke involves clinical, environmental and genetic factors ( 4 ). Advanced age, smoking, drinking, hypertension and diabetes are the risk factors to IS ( 5 , 6 ). Study indicated that the incidence of IS after the age of 40 increased evidently with age, and the susceptibility of IS in male was obviously higher than that in female in the same age group ( 7 ).…”
Section: Introductionmentioning
confidence: 99%